TAC induced cardiac hypertrophy leads to increased levels of circulating microvesicles. (25th November 2020) - Pfeifer, P; Hoelscher, M; Werner, N; Nickenig, G; Jansen, F
Abstract: Introduction: Cardiac hypertrophy and heart failure are wide spread diseases of elderly patients in the industrialised world and drive a majority of healthcare costs in these countries. Therefore, there is a high urgency to understand the development and progress of heart failure to find new therapeutic strategies especially in early stages. Microvesicles are involved in the development and propagation of almost all cardiac diseases and increased levels of circulating microvesicles can be found in blood of patients with chronic heart failure. To point out the underlying mechanisms and to provide a new animal model based approach, we investigated microvesicle (MV)-release in mice that underwent Transverse Aortic Constriction (TAC). TAC is a common method to induce cardiac hypertrophy and heart failure in mice by inducing pressure overload. We hypothesized that TAC leads to upregulation of total MV and MV of specific origin. Methods and results: Wildtype C57BL/6 mice underwent TAC to induce cardiac hypertrophy and heart failure. After TAC, mice developed cardiac hypertrophy as determined by altered heart weight/ bodyweight ratio, end-diastolic and end-systolic diameter and decreased fractional shortening. Total numbers of circulating microvesicles were detected 1, 4 and 12 weeks after TAC. We found that total numbers of circulating macrovesicles raised in a time dependent manner. Similar observations could be done with samples stained for annexin V, although results were not significant. Moreover, microvesicles were stained with specific surface markers for lymphocyte (CD3), monocyte (CD14), endothelial cells (CD31), thrombocytes (CD41), B-cells (CD45) and neutrophils (Lys6). One week after TAC increased numbers of specific microvesicles could be detected which in the course declined rapidly. Only microvesicles subgroup of lymphocyte origin showed significant increase one week after TAC-OP. Conclusion: In this study, we show that total number of circulating microvesicles raise after TAC over an observation period of 12 weeks. Furthermore, we found that increased numbers of circulating microvesicles of specific origin like lymphocytes, monocytes, endothelial cells, thrombocytes, B-cells and neutrophils showed a trend towards increased levels one week after TAC with a rapid decline in subsequent detection. To our knowledge this is the first time that the impact of TAC on number of circulating microvesicles in mice was investigated. Future studies should characterize the content and effects of these MV on recipient cells to elucidate possible contributions to heart failure progression or protective effects. Detecting new harmful or protective effects of heart failure triggered by circulating microvesicles could offer new highly needed approaches to suppress heart failure development or deliver the possibility to develop new drugs for heart failure treatment. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Else Kröner-Fresenius